Impedance spectroscopic study of Ca1-xYxTi 1-xCoxO3 ceramics based humidity sensor - Katare R.K.; Pandey L.; Thakur O.P.; Parkash O.; Kumar D. (My University, 2025)
The results of an investigation of humidity sensors based on ceramic material are discussed. It is widely approved that the ceramics based humidity sensor is superior to the polymer one due to their better thermal stability over a variety of chemical species, wide range of operating temperature and rapid response to change of humidity. Properties of humidity sensor based on ceramic system Ca1-xYxTi1-xCoxO3 are presented. The role of each part of the sensitive material in the electrical conduction process is determined based on measurements and calculated equivalent circuits. The proposed model describes the water absorption on grain and grain boundaries surfaces with very good fit to the experimental data. A new approach to the modeling of the impedance frequency dependence by means of an equivalent circuit yields very promising results for sensors. © World Scientific Publishing Company.